Industrias culturales latinoamericanas y su aporte al desarrollo social - Carolina Redondo Méndez, Andrea (Editorial Uniagustiniana, 2018)
This chapter presents opportunities that cultural in-dustries can offer to reach the desired equality in the Latin American region, based on the proposed by the Economic Commission for Latin America and the Carib-bean (eclac), regarding rights and capabilities of human beings, by recognizing contributions that can be estab-lished in terms of productivity, inclusive social develop-ment, employment generation, and social recognition in cultural subsectors. Likewise, the author shows the pri-orities of Latin American governments by looking over the social investment database for Latin America and the Caribbean. She also contrasts these priorities with alternative visions of social spending and specific cases of living conditions improvement and the inclusion of the population with successful Latin American examples of cultural industries development. This chapter reports on a qualitative research with a phase of case studies, a descriptive and explanatory process, of analytical gen-eralization. Findings show the participation of cultural industries in the search for higher levels of social de-velopment due to the contribution made by engaging population, generating employment, maximizing human capacities and achieving the reduction of poverty.